Dimensions of Service Quality in Creating Customer Satisfaction Humaira Beauty - Palupi, Tri Palupi Robustin (Jurnal Ilmu Manajemen Advantage, 2022)
Research Statista.com as of September 2020 found the share of people who don’t use makeup increased by about 2 percent. However, when the economy starts to squirm in 2021, the business is predicted to grow again. Along with the trend of Indonesians starting to make beauty products as a primary need, business opportunities in the beauty field are very large. This study aims to determine the partial and simultaneous influence of service quality dimensions on humaira beauty customer satisfaction decisions. This type of research is quantitative research with a customer population of humaira beauty. The sampling technique uses non probability sampling, namely accidental sampling, with a total sample of 40 respondents. The data analysis technique uses multiple regression analysis with the SPSS version 17 program. The results showed that: (1) There is a tangible effect on Humaira Beauty customer satisfaction; (2) There is an effect of Reliability on Humaira Beauty’s customer satisfaction; (3) There is an effect of Responsiveness on Humaira Beauty customer satisfaction; (4) There is an effect of Assurance on Humaira Beauty customer satisfaction; (5) There is no effect of Empathy on Humaira Beauty’s customer satisfaction; (6) There is a simultaneous influence of tangible variables, reliability, responsiveness, assurance, and emphaty on Humaira Beauty customer satisfaction.